Study on distortion energy and stability of gob floor based on stress deviator field. Issue 8 (21st April 2022) - Shan, Renliang; Li, Zhaolong; Wang, Chunhe; Meng, Chi; Wei, Yonghui; Li, Yongzhen; Tong, Xiao; Liu, Dong
Abstract: To analyze the plastic failure process and mechanism of gob floor in the process of close‐distance coal seams mining, a simplified mechanical model of the lateral abutment pressure of the gob was proposed to derive the stress of surrounding rock. The distribution characteristics of gob floor stress deviator were obtained, and the effect of geological parameters (coal depth H and horizontal lateral pressure coefficient λ ) were studied. By combining Mohr–Coulomb theory, the influence of surrounding rock cohesion c, internal friction angle φ, different coal seam depths H and different horizontal lateral pressure coefficients λ on the distribution of plastic zone of gob floor was obtained. The results showed that the distribution of the plastic zone under different geological factors is roughly the same as that of the stress deviator. This also proves that the excavation of the rock layer causes the redistribution of stress, which leads to the plastic failure of the surrounding rock. To verify the rationality of the proposed model, industrial experiments and simulation experiments were carried out. The results of on‐site investigation showed that the stability and integrity of surrounding rock in the concentration area of stress deviator is far less than that in the low concentration area. In addition, the acoustic wave test and the displacement field monitoring result of surrounding rock in the simulation experiments of a similar model are basically consistent with the distribution of the stress deviator field. These results agree well with the distribution of stress deviator obtained by theoretical calculation. Abstract : By means of theoretical calculation, field test, and similar simulation, this paper studies the distribution of stress deviator and the cause of plastic failure in gob floor, which is of great significance to the research of close‐distance coal mining